Meursault's anger on the problem of recognition in The Stranger by A. Camus - Maldonado Ortega, Rubén Darío (Estudios de Filosofía, 2006)
Here the itinerary of the way in which Albert Camus, making use of the Analytic of the Absurd, faces the problem of Human Liberty in an open confrontation with the Rationalist Ontological Tradition, far which he uses the Literary Recourse as a ludico-didacticai mode of expression, particularly in the episode that tells of Mersault's anger at the end of his novel The Stranger. In the development of the said itinerary, the paper will show the correspondences between the ideas that an formulated tn The Myth of Syxiphus —where the Condition pertaining to Man it established in terms of a Display of the Drama of his Absurdity, and the work of turning those ideas into suggestive images for his own recreation and his better understanding, due to his recourse to the Literary. Then the closeness between The Stranger and The Myth of Sytiphus will have to be closely studied and in relation to the formulation of a Theory of Man that creates and becomes the base for a Theory of Rebellion, expressed os Fidelity ta the Absurd. It all tends to show the concordance between the fact that the Philosophical Intuitions of Camus were expressed in Literary Form, with his thought that the Absurd Man is a Creator par excellence.